Perbandingan Model Turbulen Spalart-Allmaras dan Reynolds Stress Model pada Analisis Efisiensi dan Rugi Tekanan Siklon - Novi Caroko; Suyitno Suyitno (Semesta Teknika, 2008)
Two different turbulence models, i.e. Spalart Allmaras (SA) and Reynolds stress model (RSM) are used as turbulence model in the cyclone investigation via numerical simulation. The appropriate turbulence model is key parameter on the analysis of cyclone performance. The cyclone has a characteristic diameter of 30 cm. Four different inlet gas velocities, i.e. 13.6 m/s, 14.7 m/s, 16.3 m/s, and 17.8 m/s are simulated in FLUENT. It is found that the particle separation efficiency is higher 90% for all inlet gas velocities variation when RSM is used as turbulence model. The pressure drop is increasing linearly with the inlet gas velocity. The utilization of RSM can give better result of efficiency and pressure drop than SA turbulence model.